Preparation and keeping quality of hot smoked mackerel - Chandrasekhar, T.C., Hanumanthappa, B. and (Fishery Technology, 2021)
A method has been standardised for the production of smoke cured mackerel by dry salting in the ratio of 1:8 salt to fish followed by smoking in a traditional smoke chamber at 70±5°C for 5h. The smoke was generated by burning moist coconut husk and saw dust. The product obtained by this method had shelf-lives of 105, 95 and 6 days in chilled storage (0 to 2°C) refrigerated storage (10±2°C) and at room temperature (29±2°C) respectively.